Good news in the nuclear envelope: loss of lamin A might be a gain - Scaffidi, Paola; Misteli, Tom (The Journal of Clinical Investigation, 2006)
Genetic diseases often reveal the physiological roles of the affected proteins. The identification of mutations in the nuclear envelope proteins lamin A and lamin C as the cause of a diverse group of human diseases has expanded our understanding of the lamin proteins from being merely structural elements of the cell nucleus and has implicated them in novel cellular functions including signal transduction and gene expression. However, it now appears that the physiological relevance of one of the lamin proteins in organismal function has been overestimated. In this issue of the JCI, Fong et al. demonstrate that lamin A–deficient mice are phenotypically normal (see the related article beginning on page 743). The good news is these findings open the door to a new strategy for the therapeutic treatment of diseases caused by mutations in lamin A, such as muscular dystrophies and some types of premature aging syndromes.